RETRACTED: Close Kin Proximity in Yellowfin Tuna (Thunnus albacares) as a Driver of Population Genetic Structure in the Tropical Western and Central Pacific Ocean - Anderson, Giulia; Lal, Monal; Hampton, John; Smith, Neville; Rico, Ciro (Frontiers in Marine Science, 2019)
Recent studies argue for the presence of genetic population structure in yellowfin tuna (Thunnus albacares) in all oceans. However, the persistence of family groups has never been considered a viable mechanism of structure, nor has it been measured. We analysed genetic similarity among 280 yellowfin tunas from seven population samples collected in the Western and Central Pacific Ocean (WCPO) using single nucleotide polymorphisms, and found population structure that was significantly explained by the presence of 96 individuals involved in 332 half or full sib dyads. We found significantly higher mean and median relatedness between individuals from the same sample groups, compared to individuals from different groups; and high relatedness between individuals caught at the same fish-aggregating device (FAD) than between those caught in the wider exclusive economic zone (EEZ). Alternatively, the EEZ of the Federated States of Micronesia may harbour exceptionally large numbers of close kin. We conclude that yellowfin directly school with related individuals through their first year, and at least demonstrate tightly overlapping regional fidelity as adults. These results may explain, to some extent, the patterns of population genetic structure recently observed in yellowfin tuna.